Motivasi Petani dalam Budidaya Tanaman Pepaya (Carica papaya L.) di Kecamatan Mojosongo Kabupaten Boyolali - Pratiwi, Rahmah Indri; Suminah, Suminah; Widiyanti, Emi (AGRITEXTS: Journal of Agricultural Extension, 2022)
Papaya is one of the horticultural crops that can be developed in current cultivation because it takes advantage of Indonesia’s tropical climate and is traditionally easily cultivated by farmers. Improper post-harvest handling resulted in a low selling price of papaya in the market. This condition caused farmers to experience losses and their numbers continue to decline because they chose to stop cultivating papaya. Even though the condition of papaya farmers continues to decline, some still persist in cultivating papaya. This is closely related to the motivation of farmers. This study aims to (1) examine the motivation level of farmers in cultivating papaya, (2) examine the factors that influence farmers’ motivation in cultivating papaya, (3) examine the influence between the factors that influence the motivation of farmers in cultivating papaya plants in Mojosongo Sub-district, Boyolali Regency. The research method used is a quantitative method. The research location was chosen purposively (intentionally) to be in Mojosongo Sub-district, Boyolali Regency. The sampling method used proportional random sampling and obtained 70 respondents. Data analysis applies multiple linear regression analysis. The results of the study prove that: (1) the motivation of farmers in cultivating papaya belongs to the high category; (2) the income variable is in the very high category, land area is in the medium category, the number of family is in the medium category; (3) the variables of land area and number of family have a significant effect on farmer motivation while income has no effect.